Preparation and characterization of some new derivatives 6-bromo-2-phenylquinoline-4-carboxylic acid (Journal of the College of Basic Education, 2022)
This research includes the preparation of thirty four new derivatives of 6-bromo-2-phenylquinoline-4-carboxylic acid , and these derivatives were characterized by their melting point (C.H.N.S) Analysis , (1H-NMR) spectrum, mass spectrum, (FT-IR) spectrum. The synthesized compounds were divides into :-1- Preparation of 6-bromo-2-phenylquinoline-4-carboxylic acid 2- Preparation of 6-bromo-2-phenylquinoline-4-carboxyl chloride3-- Preparation of ethyl 6-bromo-2-phenylquinoline-4-carboxylate4- Preparation of 2-(6-bromo-2-phenylquinoline-4 carboxamido) benzoic acid5- Preparation of N-acetyl 6-bromo-2-phenylquinoline-4-carboxamide6- Preparation of 6-bromo-2-phenylquinoline-4-carbohydrazide